A Comparison of an Alternative Weight-Grading Model Against Chronological Age Group Model for the Grouping of Schoolboy Male Rugby Players - Lentin, Grégory; Cumming, Sean; Piscione, Julien; Pezery, Patrick; Bouchouicha, Moez; Gadea, José; Raymond, Jean-Jacques; Duché, Pascale; Gavarry, Olivier (Frontiers in Physiology, 2021)
Objectives: Concerns regarding marked differences in the weights and body composition of young rugby players competing within the same age groups have led to the suggestion of alternative models for grouping young players. The aim of this study was to compare variance in the body size and body composition of schoolboys rugby players, aged 9 to 14 years, across a weight- and age-grading models. Methods: Assessments of skinfold thickness were used to assess body fat mass (BF), fat-free mass (FFM), body fat mass index (BFMI) and fat-free mass index (FFMI). Standardized measure of height and weight were taken for all participants. Data were grouped according to the age categories of the French Rugby Federation (U11: Under 11 years, U13: Under 13 years, U15: Under 15 years), to the weight categories (W30-44.9; W45-59.9; W60-79.9) carried out from 25th and 75th weight percentile in each age category. BMI status (NW normal-weight versus OW/OB overweight/obese) were considered. Extreme morphotypes are characterised from BFMI and FFMI in the weight-grading model on the Hattori’s body composition chart. Results: The dispersion of anthropometric characteristics decreased significantly for the weight model, except for height in all groups and BFMI for U13. Among NW, 3%, 1.8%, 0% up-graded; 18.2%, 68.7% and 45.5% down-graded; among OW, 50%, 21.5%, 12.5% and among OB, 91.3%, 83.3%, 74.6% up-graded, respectively in U11, U13, U15. FFMI/BFMI were correlated in U11 (r= 0.80, p< 0.001), U13 (r= 0.66, p< 0.001), U15 (r= 0.77, p< 0.001). There was no significant correlation in W45-59.9 and low correlations in W30-44.9 (r=0.25, p< 0.001) and W60-79.9 (r=0.29, p<0,001). Significant grading difference between the centroids (p < 0.020) and the distribution deviates from centroids of BFMI and FFMI (p < 0.0001) were noted between the two models. Thirteen players were located in adipo-slender, twenty-three in adipo-solid, twenty-two in lean-slender, two located in the lean-solid morphotype in weight model. Conclusions: A weight-grading model should be considered to limit mismatches in anthropometric variables. The Hattori’s body composition chart allowed more detailed examination of morphological atypicalities among schoolboy rugby players.